Stylistic Use of Phraseological Units in Discourse - Naciscione, Anita (John Benjamins Publishing Company, 2010)
This interdisciplinary study presents the cutting-edge state of theoretical and applied research in phraseology. The author elaborates key terminology and theoretical concepts of phraseology, while challenging some prevailing assumptions. Exploration of phraseological meaning across sentence boundaries is supported by ample textual illustrations of stylistic use ranging from Old English to Modern English. The book contains innovative research in the discourse-level features of phraseological units from a cognitive perspective, along with creative use of phraseological metaphor, metonymy and allusion, including multimodal discourse. The author argues for the need to raise stylistic awareness among teachers and learners, translators, lexicographers and advertisers. This is the revised and extensively expanded new edition of 'Phraseological Units in Discourse: Towards Applied Stylistics' (2001). It received honourable mention at the ESSE Book Award 2012.